Landasan Sosiokultural untuk Memperkuat Pengembangan Kurikulum PAI dan Budi Pekerti di Sekolah Menengah Atas - Nuroh, Laelatul (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
This research analyzes how the Islamic Religious Education (PAI) curriculum and moral values at the high school level can be improved by considering sociocultural factors. The results show that the PAI curriculum emphasizes the importance of social and cultural interactions in the learning process. This curriculum is adapted to individual environments and is expected to evolve with environmental changes, aiming to shape personalities and mindsets aligned with religious values. Social and cultural interaction is considered integral to the learning process in Islamic education, which also focuses on fostering religious enthusiasm and attitudes. The goal is to develop all human potential to achieve the ultimate goal of education: creating perfect humans (insan kamil). The curriculum includes intra curricular, co-curricular, and extracurricular activities to enhance education. The development process follows four stages: formulating objectives, selecting learning experiences, organizing learning experiences, and evaluating learning experiences. High school curriculum development involves creating religious programs for short, medium, and long-term goals to form students with a solid understanding of religion and noble character (Akhlakul Karimah).